Energy trends and the water-energy binomium for Brazil - Rocha,Gisele O. Da (2015)
According to the demands of energy saving and carbon emission reduction, the water vs. energy nexus has become a major concern worldwide. Brazil occupies a singular position in the global energy system. A major portion of the Brazilian occupancies has electricity and the energy system expansion that, at first, possesses adequate means for supporting the economic growing may experience some turnovers. The Brazil determination through alternative fuels was a natural choice, given its large hydropower potential and land agricultural base. In the transportation sector Brazil has developed its energy matrix towards an important rate of ethanol and biodiesel. Although those fuels are low carbon emitter, they may probably not be an affordable alternative regarding land use, food security and water footprint. In this way, considering the recent advances in the exploration of oil from Pre-salt (9-15 million barrels) and the discovery of shale gas wells up to 245 tcf, together to unfavorable social and environmental issues associated to biofuels, the Brazilian energy matrix might turn back to the fossil fuels again. These represent challenges to the Brazilian policymakers and how they will be solved will reflect not only in Brazil but also to the world at large.